REDUCING THE ENERGY CONSUMPTION OF SYSTEMS WITH THE INTEGRATED CIRCUIT TI 430FR2433 - DAN ROTAR; DRAGOS-ALEXANDRU ANDRIOAIA (Journal of Engineering Studies and Research)
The Texas Instruments microcontrollers in the MSP 430 series offer four ways to save power in operation in such a way as to allow for consistent reduction of the electricity consumed. Code Composer Studio programming environment also provides support in making low-power applications. In addition to these, the MSP430FR2433 microcontroller with ferroelectric RAM allows data to be stored even in the absence of power voltage. In view of these properties of the microcontroller, a data logger application has been developed to monitor the quality of the environment in a building. Given that the MSP430FR2433 microcontroller can process both analog and numerical signals, the device monitors the temperature, humidity, carbon dioxide concentration and amount of light present in the enclosure. Thanks to energy-saving mechanisms and the possibility of keeping information for an indefinite period without the need for energy consumption, the ambient quality monitoring device can operate for a long time in places without energy resources. The device has also been tested with good results for autonomous operation using solar energy and has also been used to determine the energy performance of buildings.